2014
DOI: 10.1590/0103-0582201432210313
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respiratory muscle strength in children according to the classification of body mass index

Abstract: OBJECTIVE: To assess and compare the respiratory muscle strength among eutrophic, overweight and obese school children, as well as to identify anthropometric and respiratory variables related to the results. METHODS: Cross-sectional survey with healthy schoolchildren aged 7-9 years old, divided into three groups: Normal weight, Overweight and Obese. The International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire was applied. The body mass index (BMI) was evaluated, as well as the forced expi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
8
0
4
Order By: Relevance
“…In Santa Catarina, Brazil, Rosa and Schivinski [16] observed healthy and normal school children, and identified a strong relationship among obesity, overweight and RMS. In asthmatic obese adults, Mosen et al [17] observed that it is related to reduced quality of life, lack of control and increased hospitalization in obese patients if compared to nonobese asthmatics.…”
Section: Resultsmentioning
confidence: 98%
“…In Santa Catarina, Brazil, Rosa and Schivinski [16] observed healthy and normal school children, and identified a strong relationship among obesity, overweight and RMS. In asthmatic obese adults, Mosen et al [17] observed that it is related to reduced quality of life, lack of control and increased hospitalization in obese patients if compared to nonobese asthmatics.…”
Section: Resultsmentioning
confidence: 98%
“…An interval of 30 seconds occurred after each maneuver. Between the measurement of MIP and MEP, a three-minute interval occurred to avoid the patient's fatigue 12 . The data obtained were compared with the data proposed in the reference equations by Rosa et al 13 for children aged between six and ten years.…”
Section: Methodsmentioning
confidence: 99%
“…The expiratory flow limitation leads to a dynamic hyperinflation, creating an auto-PEEP, in relation with the incomplete expiration (61,62). Also, the strength of respiratory muscles is affected in obesity (63,64). Finally, in the context of obesity, lung bases are under-ventilated but over-perfused, creating a ventilationperfusion mismatch (65).…”
Section: Severitymentioning
confidence: 99%